Anoxic sediments of the Kveithola Trough, Barents Sea (Arctic region), micropaleontological and sedimentological evidences. - GAMBOA-SOJO, VIVIANA MARIA (Pisa University, 2017)
Abstract The glacially influenced Kveithola Trough is an abrupt narrow sedimentary system located in the NW Barents Sea. Along with the larger Storfjorden glacial system, it hosted, during the last glaciation, ice streams draining ice from the southern Svalbard in the north and Bear Island in the south. The Kveithola Trough has specific morphological and depositional features, a shallow water counturite drift that forms geographically well confined depocenters. The drift consists of two main depocenters separated by the relief of a buried grounding-zone wedge. Here a distinct moat can be identified, which implies the strong influence of dense bottom currents, inferred to flow (or at least to have flown in the past) towards the outer shelf. The highly dynamic environment depicted from the morphological and structural characteristics of the sediment drift is in contrast with the sediment facies and preserved biota observed in the surface sediments of the Kveithola drift. The analysis of 4 box-corers collected during the oceanographic cruise EUROFLEETS”-BURSTER revealed that surface sediments in the innermost part of the Kveithola Trough are fine-grained, soft and soupy with a “jelly-like” consistency. The cored sediments are mostly black, organic matter-rich, with presence of abundant H2S, abundant black worm tubes (Siboglinidae worms) and occasionally with living reddish polychaetes (possibly ampharetid polychaetes). The recent (about last 2000 years) benthic foraminiferal assemblage observed in the sediments is characterized by the presence of low-oxygen species as Globobulimina auriculata and opportunistic species (among others Nonionellina labradorica), indicating stressed environments. The sediments of the Kveithola Drift that deposited under persistent dense bottom currents, thus, appears today as a stagnant environment strongly affected by low-oxygen conditions with likely ongoing seep activity. The jelly-like consistency of the sediments may be related to “organic matter-sediment-pore water bound” in ...